An analytical instrument for coding and assessing argumentative dialogues in science teaching contexts. Issue 3 (10th February 2022) - Martins, Marina; Macagno, Fabrizio
Abstract: Most of the tools developed in the area of Science Education aimed at analyzing either the product or the process of argumentation do not consider the following: (a) arguments are a part of dialogues, (b) dialogues present different objectives, (c) dialogues start from different assumptions, and (d) dialogues shape the roles and moves of interlocutors. This paper intends to address the analysis of argumentative exchanges within educational science dialogues considering several aspects of argumentation that have neglected to be investigated in the field of education, such as the relations among individual moves and the dialogues they are part of, and the influence of such moves on knowledge construction. Toward this purpose, a proposed tool is presented, which describes argumentative dialogues in science teaching contexts across the varied and interrelated dimensions. This tool, consisting of six analytical aspects, is applied to high school chemistry students' argumentative dialogues taking place during modeling activities. Data collection (involving audio and video recording plus observations made by the researchers) revealed the main affordances of this tool as follows: (a) favoring an understanding of the individual and collective students' intentions; (b) enabling the characterization of argumentative discourse beyond the moves of refuting, questioning and providing support; (c) enabling the identification of whether knowledge construction has occurred; and (d) the possibility of analyzing teaching situations across different contexts. Thus, the tool supports the descriptions and analyses of the scientific argumentation process and the associated knowledge construction by students.